A study on Retailing of Leather Products in Vellore District (International Journal of Scientific Research and Management (IJSRM), 2013)
Using survey method, the present study aims at finding out the marketing activities carried out by the retailers of leather products, the price range, which their customers prefer, factors considered by buyers while making a buy and factors which contribute to success of business. Findings indicate, customers prefer high price goods, retailers rely on price reduction and discount but not on credit facility. Customers decide on the basis of product design but reasons for success of business are mainly found to be price and quality.